Supporting Egypt’s safety net programs for better nutrition and food security, inclusiveness, and effectiveness - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2021)
The long partnership between the Government of Egypt and the International Food Research Institute (IFPRI) began in the late 1970s but became much more active with the launch of IFPRI’s Egypt Strategy Support Program (ESSP) in 2016. Over the years, IFPRI’s research, with support from PIM since 2012, has informed important decisions on Egypt’s key safety net programs, including the food subsidy and the national cash transfer programs. This summarizes some of the most recent outcomes of this work.